Utilizing LMS for EFL reading classes: A student survey approach - Sindi Tia Umarlinda; Irwan Sulistyanto; Erwin Hari Kurniawan (Celtic : A Journal of Culture, English Language Teaching, Literature and Linguistics, 2025)
This study explores students’ perceptions of university Learning Management System (LMS) in English learning, particularly in supporting reading activities. Using a quantitative descriptive design, data were collected from 2nd, 4th, and 6th semester English education students through a structured questionnaire. The instrument consisted of closed-ended Likert scale questions and an open-ended question for suggestions. Data were analyzed using SPSS version 27 for descriptive statistics, and open-ended responses were thematically summarized. Findings indicate that students generally perceive LMS positively regarding usefulness, ease of use, ease of learning, and satisfaction. They found it helpful for managing assignments, accessing materials, and supporting independent learning. However, suggestions from students highlight areas for improvement, such as adding notification features, improving server reliability, simplifying the interface, and providing user training. These results reflect the importance of not only technical functionality but also user experience in educational technology. The findings contribute to the field of English language learning by emphasizing the role of LMS in facilitating reading comprehension and learner autonomy. This study also offers practical implications for LMS developers and educators, encouraging more user-centered design and continuous improvement to optimize digital learning environments in higher education.